2018
DOI: 10.1182/blood-2017-11-742577
|View full text |Cite
|
Sign up to set email alerts
|

The MYC oncogene is a global regulator of the immune response

Abstract: The MYC proto-oncogene is a gene product that coordinates the transcriptional regulation of a multitude of genes that are essential to cellular programs required for normal as well as neoplastic cellular growth and proliferation, including cell cycle, self-renewal, survival, cell growth, metabolism, protein and ribosomal biogenesis, and differentiation. Here, we propose that MYC regulates these programs in a manner that is coordinated with a global influence on the host immune response. MYC had been presumed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(136 citation statements)
references
References 118 publications
3
133
0
Order By: Relevance
“…This result supports previous studies that have shown BET inhibition to boost antitumor immune responses, and suggests that targeting BET proteins in combination with immune checkpoint inhibitors may potentially elicit a synergistic response (34). Furthermore, c-MYC-driven tumors are reported to have intrinsic tumor cell autonomous regulation and suppression of both innate and adaptive immune responses, and inhibition of MYC restores immune responses to tumor cells (35).…”
Section: The Effects Of Bet Degraders On Gene Transcriptionsupporting
confidence: 87%
“…This result supports previous studies that have shown BET inhibition to boost antitumor immune responses, and suggests that targeting BET proteins in combination with immune checkpoint inhibitors may potentially elicit a synergistic response (34). Furthermore, c-MYC-driven tumors are reported to have intrinsic tumor cell autonomous regulation and suppression of both innate and adaptive immune responses, and inhibition of MYC restores immune responses to tumor cells (35).…”
Section: The Effects Of Bet Degraders On Gene Transcriptionsupporting
confidence: 87%
“…Our analyses with immune‐poor melanomas stratified by MITF immunostaining suggested transcriptional upregulation of β‐catenin‐dependent canonical Wnt signaling pathway along with the upregulation of c‐Myc in the MITF‐positive group. Immune evasion through upregulation of canonical Wnt signaling pathway is common in melanomas (Spranger et al , 2015), and the role of c‐Myc in the immune exclusion process has previously been described (reviewed in Casey et al , 2018). Since β‐catenin‐induced melanomas require functional MITF (Schepsky et al , 2006; Widlund et al , 2002) and loss of MITF expression affects the corresponding expression of c‐Myc (Seoane et al , 2019), thus the role of MITF seems important in distinction of the immune evasion mechanisms in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of MYC family of genes has been shown to sensitize tumors to Aurora kinase inhibitors [17]. MYC, MYCN, and MYCL are three versions of a family of genes that regulate multiple activities involving cell cycle, growth, metabolism, differentiation, apoptosis, transformation, and immune-regulation [18,19]. Although JAZF1-MYCL1 fusion has never been characterized before, a similar fusion involving RLF-MYCL1 has been well characterized in SCLC samples [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest MYC as a central regulator of global tumor-immune response. MYC-dependent tumors may be sensitive to immunotherapeutic agents and MYC expression may be a good biomarker for such sensitivity [19]. In addition to these, BET inhibitors appear to target MYC dependence in various malignancies by downregulating transcription of MYC, MYC-dependent target genes, and CD274 (encoding PD-L1) [28,29], and their action was synergistic when used in combination with PD-L1 blockers [30,31].…”
Section: Discussionmentioning
confidence: 99%